Penerapan Model Pembelajaran Call on The Next Speakers (Memanggil Pembicara Berikutnya) Untuk Meningkatkan Hasil Belajar Matematika Siswa Pada Materi Komposisi Fungsi dan Fungsi Invers - Sulastri Sulastri (Program Studi Magister Pendidikan IPA, Universitas Mataram, 2023)
The purpose of this study was to improve students' mathematics learning outcomes in the matter of function composition and inverse functions in Class XI MIA 4 SMA Negeri 3 Sumbawa Besar with the Application of the Call on The Next Speakers Learning Model. This research is included in the form of Classroom Action Research (CAR) and is carried out in 2 cycles, namely Cycle I and Cycle II. Each cycle consists of planning, action, observation, and reflection. The data to be collected in this study is the research aspect, namely the Application of the Call on The Next Speaker Model and student learning outcomes. The results of the study show that: (1) Implementation of learning in the Mathematics subject material Algebraic Operations Function through the application of the Call on The Next Speaker learning model (calling the next speaker) in class XI MIA 4 SMA Negeri 3 Sumbawa Besar can increase student learning activities. This is based on observations of all indicators that have been determined in cycle I showing an average student learning activity of 58.16%, the category is sufficient, increasing to 70.92%, the good category in cycle II has exceeded the indicators of completeness of activities classically set in this study. ie 66% -79% good category. The increase in student learning activities from cycle I to cycle II was 12.76%; (2) Implementation of learning in the Mathematics subject matter of Inverse Functions through the application of the Call on The Next Speaker learning model (calling the next speaker) in class XI MIA 4 SMA Negeri 3 Sumbawa Besar can improve students' mathematics learning outcomes. This is based on the results of the posttest in cycle I obtained an average value of 74.90 with the percentage of students who completed KKM by 62.86% experienced an increase in cycle II with an average value of 79.89 and the percentage of students who completed KKM was 85 .71% has exceeded the classical success indicator set in the study, namely 85%.